The burden of epilepsy in the People’s Republic of China from 1990 to 2019: epidemiological trends and comparison with the global burden of epilepsy - Shu, Yun; Wu, Zhifeng; Yang, Xiaolin; Song, Min; Ye, Yangyang; Zhang, Chunqing; Yuan, Qing; Wang, Li (Frontiers in Neurology, 2023)
Background Epilepsy is associated with a significant global burden of disease, affecting over 50 million people worldwide. The specific aim of this study is to compare the burden of epilepsy in the People’s Republic of China (PRC) with the global burden, and to analyze the epidemiological trends of epilepsy, the relationship between the burden of epilepsy and social demographic index (SDI), and the relative contributions of epidemiological factors. Methods This is a retrospective population-based study, data were obtained from the Global Burden of Disease (GBD) study in 2019. We employed Joinpoint software and the age-period-cohort (APC) model to analyze epilepsy’s epidemiological trends. Health inequality analysis was conducted to investigate the impact of SDI on epilepsy burden. Decomposition analysis was performed to examine the relative contributions of age, population, and epidemiological changes to epilepsy. Results Between 1990 and 2019, the incidence rate in the PRC increased by 45%, significantly surpassing the global incidence of epilepsy. However, Disability-Adjusted Life Years (DALY) decreased notably, and the proportion of Years of Life Lost (YLL) decreased from 62.73 to 39.03%. Concerning incidence, the period Rate Ratio (RR) in the PRC initially increased and then decreased, while the cohort RR in the PRC and globally exhibited a consistent upward trend. In terms of mortality, period RR and cohort RR in the PRC displayed a gradual decrease, with mortality starting higher but eventually falling below the global mortality. The net drifts of incidence were greater than 0, whereas the net drifts of mortality were less than 0, both were lower in the PRC than at the global level. Decomposition analysis indicated that the changes of incidence and mortality in the PRC were mainly attributed to epidemiological changes. Additionally, global disparities in epilepsy decreased, with the burden concentrating in low SDI countries. Conclusion The incidence of epilepsy in the PRC rose during the 30-year study period, while epilepsy mortality decreased. The improved survival rate in the PRC is predominantly attributable to epidemiological changes. The burden of epilepsy in the PRC predominantly affects males, children, and the elderly, Chinese government should focus on specific populations.